Prospective Analysis of Seaweed Processing Downstream Business: A Case Study in Lontar Village - Gumilar, Iwang; Saputra, Adjie; Anggraeni, Santi Rukminita; Pratama, Rusky Intan; Maulina, Ine (Sam Ratulangi University, 2024)
Seaweed grows in almost all waters of Indonesia, making it one of the important exporting countries in Asia. Indonesia's three main seaweed export commodities are Eucheuma cottonii, Gracillaria sp., and Gelidium sp. One significant seaweed cultivation center is Lontar Village. However, value-added downstream product activities still need to be developed there. The potential for drying seaweed in Lontar Village reaches 150,000 kg per month. Data analysis was performed using quantitative descriptive methods, including profitability analysis, B/C Ratio analysis, Break-Even Point analysis, and Payback Period over the past year with five harvest cycles. The prospective analysis results include aspects of seaweed drying processing techniques, financial elements, and marketing aspects. This study uses a case study method with key informants being the head and members of the seaweed processing group in Lontar Village. The data used are from five harvest cycles over the past year. The prospective analysis results show that the financial analysis of the seaweed processing business in Lontar Village indicates positive outcomes, such as positive profits, a B/C Ratio greater than 1, seaweed sales and production values exceeding the Break-Even Point, and a Payback Period of less than one year. Seaweed marketing in Lontar Village is conducted on a cash basis, with their main market being Java Island. Keywords: Prospective, Business, Processing, Seaweed. Abstrak Rumput laut tumbuh hampir di seluruh perairan Indonesia, menjadikannya salah satu negara pengekspor penting di Asia. Tiga komoditas ekspor utama rumput laut Indonesia adalah Eucheuma cottonii, Gracillaria sp., dan Gelidium sp. Salah satu sentra budidaya rumput laut yang signifikan adalah Desa Lontar. Namun, kegiatan hilirisasi produk jadi yang bernilai tambah masih perlu dikembangkan di sana. Potensi penjemuran rumput laut kering di Desa Lontar mencapai 150.000 kg per bulan. Analisis data dilakukan menggunakan metode deskriptif kuantitatif, yang meliputi analisis keuntungan, analisis B/C Ratio, analisis Break Even Point, dan Payback Period selama satu tahun terakhir dengan lima siklus panen. Hasil analisis prospektif mencakup aspek teknik pengolahan penjemuran rumput laut, aspek finansial, dan aspek pemasaran. Penelitian ini menggunakan metode studi kasus dengan informan kunci berupa ketua dan anggota kelompok pengolahan rumput laut di Desa Lontar. Data yang digunakan adalah data dari lima siklus panen selama satu tahun terakhir. Hasil analisis prospektif menunjukkan nalisis finansial usaha pengolahan rumput laut di Desa Lontar menunjukkan hasil yang baik, seperti keuntungan yang bernilai positif, B/C Ratio lebih dari 1, nilai penjualan dan produksi rumput laut lebih besar dari nilai Break Even Point, dan Payback Period kurang dari satu tahun. Pemasaran rumput laut di Desa Lontar dilakukan dengan sistem kontan, dan pasar utama mereka adalah Pulau Jawa. Kata kunci: Prospektif, Usaha, Pengolahan, Rumput Laut.